Adherence in patients in the first year after kidney transplantation and its impact on graft loss and mortality: a cross‐sectional and prospective study. (22nd May 2014) - Prihodova, Lucia; Nagyova, Iveta; Rosenberger, Jaroslav; Majernikova, Maria; Roland, Robert; Groothoff, Johan W.; van Dijk, Jitse P.
Abstract Aims To explore the predictive value of adherence to their immunosuppressive medication in kidney transplant recipients in the first year after kidney transplantation as a determinant of graft loss and mortality up to 12 years (prospective analysis) and its association with sociodemographic and medical factors and social support (cross‐sectional analysis). Background Poor adherence to their immunosuppressive medication in kidney transplant recipients remains the leading preventable cause of poor patient outcomes. Design Prospective and cross‐sectional study. Methods At baseline, 325 patients 3–12 months posttransplantation were invited to participate. Adherence was assessed using collateral reports – a combination of patients' self‐evaluation and an estimate by their nephrologist. The patients provided sociodemographic and medical data and completed the End‐Stage Renal Disease Symptom Checklist and Multidimensional scale of perceived social support. At follow‐up (average 7·1 years), data on patients and graft survival were obtained. All data were collected from 2002–2013. Multinomial regression analysis and Cox regression were performed. Results A total of 297 patients (48·1 (12·8) years, 61·6% men) agreed to participate (response rate 91·4%); 67·4% were considered as fully adherent. Poor adherence was associated with higher risk of graft loss and mortality over 12 years. Female sex, higher education, higher perceived side effects of corticosteroids, better perceived cardiac and renal function and higher perceived family social support in the first year posttransplantation were associated with full adherence to immunosuppressive treatment. Conclusions Patients with poor adherence to the immunosuppressive medication in the first year after kidney transplantation showed increased likelihood of graft loss and death over 12 years compared with the adherent patients.